Construction Process Simulation and In Situ Monitoring of Dendritic Structure on Nanjing Niushou Mountain - Wenying Zhang; Shaole Yu; Xuewei Zhang; Junsheng Yan; Xinxi Chen (Shock and Vibration)
For complex structures, where there are great differences between the structural form in the construction process and the design forming state, mechanical analysis of the construction process is required. The dendritic structure on Nanjing Niushou Mountain is taken as an engineering case study, with a narrow construction space, weak construction platform, and difficulty in setting the equipment in the site. A new construction method, self-balancing elevating scheme, is introduced according to the special condition of the construction field. The lifting frame and the connection joint between the trunk and the branch employed in the self-balancing elevating scheme are optimized according to the structure’s behavior. A construction monitoring scheme was adopted in this project to ensure construction safety. The maximum cable force and deformation occurred at the beginning of the lifting. The construction process simulation was conducted by space structure design software 3D3S. The analysis results were well consistent with the in situ construction monitoring results. The analysis results show that the self-balancing elevating scheme could satisfy the construction requirement on the special construction condition and provide reference on future practical application.